Perlakuan Akuntansi Pembiayaan Ijarah berdasarkan PSAK no.107 (Studi Kasus BMT Rizqona Ikabu Tambakberas Jombang) - Nur, Imada; Susilo, Dwi Ermayanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
BMT Rizqona Ikabu Tambakberas Jombang is a sharia people's bank that has a variety of financing products, one of which is ijarah financing. The purpose of this financing is to meet customer needs on a consumptive basis.This study aims to analyze the accounting treatment of ijarah financing based on PSAK No. 107 (a case study of BMT Rizqona Ikabu Tambakberas Jombang). To reveal the problem as a whole, researchers used descriptive qualitative methods with data collection techniques in the form of observation, interviews and documentation. From the results of research that has been done that the accounting treatment for ijarah financing based on PSAK no.107 (a case study of BMT Rizqona Ikabu Tambakberas Jombang) in its practical activities is in accordance with PSAK no.107. in accordance with the indicators of PSAK no.107 accounting for recognition and measurement, presentation and disclosure are in accordance with PSAK no.107 except in the case of the accounting records of recognition and measurement of repair or maintenance of ijarah objects the lessee does not recognize and measure these costs